Can Eye Movements Be a Predictor of Implicit Attitudes? Discrimination Against Disadvantaged Individuals During the Recruitment Process - Çelik, Samet; Turker, Malik Volkan; Çelik, Samet (Istanbul Univ, Sch Business, 2022)
The present study examined the effect of eye movements during the recruitment process with eye-tracking technology as an indicator of negative implicit attitudes against disadvantaged groups. We composed eleven fictional resumes, and we asked the recruitment experts to hire the most suitable candidate for the position in the laboratory environment. The study used a mixed-methods approach. First of all, we evaluated the psychosocial characteristics of the participants. Then, we recorded the eye movements of the participants during the recruitment process. Lastly, we held interviews with the participants about their choices. We concluded that the recruitment experts had spent more time examining the social identities of the candidates than the candidate's work experiences and educational background. Furthermore, we also found that the disadvantageous social identities of these candidates were more influential in the recruitment process. As a result, we can say that our implicit attitudes affect our behaviors and preferences, and eye movements can be a useful tool in predicting intentions and implicit attitudes.
Can Eye Movements Be a Predictor of Implicit Attitudes? Discrimination Against Disadvantaged Individuals During the Recruitment Process
Keywords: Discrimination In The Workplace; Eye Movements; Human Resource Management; Hrm; Implicit Attitudes